IMPLEMENTASI UNDANG-UNDANG INFORMASI DAN TRANSASKSI ELEKTRONIK DALAM RANGKA MENCEGAH DAN MENANGGULANGI KAMPANYE HITAM (BLACK CAMPAIGN) TERKAIT PEMILIHAN KEPALA DAERAH SERENTAK 2018 - Pane, Musa Darwin (Universitas Komputer Indonesia, 2020)
This study aims to determine the enforcement of the Information Act and Electronic Transactions in tackling the black campaign with normative juridical research methods that start from the norms, principles and legislation that exist as positive legal norms. This study concludes that the implementation of the Information and Electronic Transaction Law in the case of black campaigns between the rights is in accordance with the Articles contained in the Electronic Information and Transaction Law (ITE) including Article 27 paragraph (3) in conjunction with Article 45 paragraph (3) of the Act Information and Electronic Transactions and Article 28 paragraph (2) juncto Article 45A paragraph (2) of the Electronic Information and Transaction Law. That according to this research the black campaign is interpreted as an attempt to fill certain positions, especially public positions in unhealthy ways, such as spreading hoaxes, sheep fighting, insults and slander. Black campaigns clearly violate the law and ethics in campaigning, besides the use of black campaigns in social media is felt to be very effective in bringing down political opponents so that in the elections the use of black campaigns violates the principle of fair play / justice. Key words: Black Campaign, the Law on Information and Electronic Transactions